Diabetic ketoacidosis in vanishing white matter. Issue 8 (17th June 2016) - Alamri, Hannadi; Al Mutairi, Fuad; Alothman, Johara; Alothaim, Ali; Alfadhel, Majid; Alfares, Ahmed
Key Clinical Message: Clinicians should consider the EIF2B1 gene defect in any patient with diffuse white matter disease on an MRI of the brain and DKA. Abstract : Clinicians should consider the EIF2B1 gene defect in any patient with diffuse white matter disease on an MRI of the brain and DKA.